Educação musical soando na escola: transitando entre turno e contraturno numa escola de Caucaia-CE - Sombra, Daniel do Nascimento (2018)
The present research brings a reflection about the potentialities involved in the relationship between the music teacher acting in extra classes on a second shift and eight pedagogy graduates who teach the initial grades of elementary school in a public institution in the municipality of Caucaia, seeking to respond the questioning “how can a music teacher and pedagogy graduates, in an integrated way, provide musical education for their students of primary education?” through the analysis of a didactic proposal. It is intended to follow this path through a case study, investigating the impact of a proposal of music education based on the development of the dimensions of musicality in which the music teacher interacts simultaneously with the pedagogy graduates and their students, in the context of music classes in a primary education school in Caucaia, through the description of the process of planning and application of classes taught during the research, collecting data through a report made by the music teacher and narrative interviews with the teachers involved in the research and analyzing the concepts of the praxeology and philosophy of musical education, so that the use of music can be expanded in elementary school, broadening the limits of the field of primary education by integrating the subfield of musical education through the development of the participant’s dimensions of musicianship so that the musical education project is integrated to the school community. The interaction between the pedagogy graduates and the music teacher is one of the first assumptions of the study. This research corroborates the participation of the music teacher in the schools of the municipality of Caucaia so that their performance is not isolated from the pedagogical project of the schools. Thus, the music teacher can contribute to music education by relating it to the school community in a diversified and comprehensive way, just as the pedagogy graduates can benefit from a musical learning that reinforces their practice in the classroom.